Synthesis Of Methyl Acetate By Lipase Catalyzed Esterification - Izudin @ Mohamad, Muhammad Firdaus (Universiti Sains Malaysia, 2021)
The beginning of esterification process is mostly by using chemical synthesis with the help of chemical catalyst which often involved binary or tertiary azeotropic mixture which lead to difficulty in producing high purity of product and environmental issues. Hence, esterification with the aid of biocatalyst was introduced which is proven to have a better potential especially with lipase in producing esters through enzymatic esterification. In this study, methyl acetate which has high market demand due to its end uses was synthesise by direct esterification reaction catalysed by immobilized lipase from Candida rugosa by using n-hexane as organic solvent in batch system. Celite-545 was used as a support material on immobilized Candida rugosa lipase with catalytic activity of 0.6833 U/mg. One-Factor-at-One-Time (OFAT) method was studied in order to identify the effect of the optimizing parameters including reaction time, enzyme loading, agitation speed and substrate molar ratio of acetic acid and methanol. The optimal acid conversion for methyl acetate was 58% obtained at 2 hours incubation time with 10 U/ml of enzyme loading at 45 and 150 rpm of agitation speed with a substrate molar ratio of 1:3 (acetic acid to methanol). The comparison between kinetic models of enzyme catalysed esterification with the secondary data from the article was also performed by using non-linear regression analysis.